Economic and Biological Characteristics of Tomato Varieties, Hybrids When Growing in Film Unheated Greenhouses - Turaev J. M; Lyan E.E; Kim V.V (Zien Journals, 2022)
This article presents the results of testing a collection of tomatoes of foreign and local selection in film unheated greenhouses. Testing of tomato varieties in film greenhouses showed that many promising samples are a valuable source material for creating early-ripening, highly productive and high-tasting disease-resistant tomato fruits
Keywords: Film greenhouses; varieties; hybrids; tomatoes